PILIHAN HUKUM WARIS BAGI ORANG DI INDONESIA BERAGAMA ISLAM - Bambang Yunarko (Perspektif, 2005)
Authoritative give and break the heir case for Indonesia people which believe in the Islam based interest of absolute Religion Court, Section 49 sentence 1 Number Law 7 Year 1989, residing in Religion Court, while choice of hereditary law for Indonesia people which believe in the Islam pursuant to number 2 sixth paragraph public Clarification of Number Law 7 Year 1989 can only be done outside Jurisdiction Body.